2009
DOI: 10.1063/1.3114989
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical investigations of periodically polarity inverted ZnO heterostructures on (0001) Al2O3

Abstract: We report the structural and optical properties of one-dimensional grating of ZnO consisting of periodically polarity inverted structures on (0001) Al2O3 substrates. The inversion domain boundaries (IDBs) between the Zn- and the O-polar ZnO regions were clearly observed by transmission electronic microscopy. The investigation of spatially resolved local photoluminescence (PL) revealed strong excitonic emission at the interfacial region including the IDBs. The possible mechanism of strong PL has been discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…On the other hand, the reversal of polarity across interfaces is also possible in various semiconductors. The periodically polarity-inverted ZnO heterostructures on (0001) Al 2 O 3 reveal strong exitonic emission at the interface region 12 . Polarity inversion of GaN is realized by deposition and patterning of a thin low-temperature AlN nucleation layer 13 .…”
mentioning
confidence: 96%
“…On the other hand, the reversal of polarity across interfaces is also possible in various semiconductors. The periodically polarity-inverted ZnO heterostructures on (0001) Al 2 O 3 reveal strong exitonic emission at the interface region 12 . Polarity inversion of GaN is realized by deposition and patterning of a thin low-temperature AlN nucleation layer 13 .…”
mentioning
confidence: 96%
“…7͑a͒. Park et al 24 reported the inversion domain boundary formation between both polar region in similar structured PPI ZnO structures. In this time, we want to focus on the transition regions to find out the origin of anisotropic broadening of FWHM of ZnO ͑0002͒.…”
Section: Resultsmentioning
confidence: 97%
“…6 shows temperature dependent PL spectra obtained from PPI ZnO structures with 500 nm period. Before the temperature variation, the m-PL spectra obtained from both polar region and interface region between Zn-and O-polar at 77 K. The interface region shows the highest PL intensity among measured regions which is related to the physical geometry or diffusion length difference depending on Zn-and O-polar regions [8].…”
Section: Structural and Optical Properties Of Ppi Znomentioning
confidence: 99%
“…4(a). The detailed interfacial properties between Zn-and O-polar regions can be found in elsewhere [8].…”
Section: Structural and Optical Properties Of Ppi Znomentioning
confidence: 99%
See 1 more Smart Citation